2004
DOI: 10.1111/j.1365-3164.2004.00414_66a.x
|View full text |Cite
|
Sign up to set email alerts
|

P‐66A 
Thermographic aspects of feline fibrosarcoma complex

Abstract: Skin physiology in cats has received little attention. The aim of this study was to evaluate the long-term influence of sex, time and the level of dietary fat and energy on the dynamics and qualities of the hair coat. Twenty-four European short-haired laboratory cats were followed over a 1-year period. They were divided into eight groups of three, according to: sex (12 males and 12 females), sexual status (intact or neutered) and diets [(high energy 4300 kcal/kg as fed, 21% fat) vs. (moderate energy 3500 kcal/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Higher temperatures (up to 5°C) in a FISS vs surrounding tissues have been reported elsewhere. 20,21 Temperatures detected in TA and nTA did not differ significantly in the FISSs in this sample. Still, thermographic patterns varied widely between these tumors.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Higher temperatures (up to 5°C) in a FISS vs surrounding tissues have been reported elsewhere. 20,21 Temperatures detected in TA and nTA did not differ significantly in the FISSs in this sample. Still, thermographic patterns varied widely between these tumors.…”
Section: Discussionmentioning
confidence: 69%
“…Higher temperatures (up to 5°C) in a FISS vs surrounding tissues have been reported elsewhere. 20,21…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to human medicine, the application of IRT to assess vascular compromise in veterinary medicine is still developing, and limited studies have been published. However, it has been suggested that identifying an altered local temperature response in animals might help to recognize blood perfusion disorders such as vasculitis [ 11 ] or even discern between benign and malign neoplasia [ 12 , 13 ]. For example, aortic thromboembolism cases in cats show a hypothermic response in pelvic limbs, a method that can serve to differentiate between healthy animals and those affected by the pathology [ 14 ].…”
Section: Introductionmentioning
confidence: 99%